2016
DOI: 10.5830/cvja-2015-049
|View full text |Cite
|
Sign up to set email alerts
|

Filamin C: a novel component of the KCNE2 interactome during hypoxia

Abstract: SummaryAimKCNE2 encodes for the potassium voltage-gated channel, KCNE2. Mutations in KCNE2 have been associated with long-QT syndrome (LQTS). While KCNE2 has been extensively studied, the functions of its C-terminal domain remain inadequately described. Here, we aimed to elucidate the functions of this domain by identifying its protein interactors using yeast two-hybrid analysis.MethodsThe C-terminal domain of KCNE2 was used as bait to screen a human cardiac cDNA library for putative interacting proteins. Co-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Neethling, et al reported that KCNE2, which is a voltage-gated potassium channel and functions in ven-tricular repolarization, interacted with FLNC. 28) Given the collective evidence, the sudden deaths in this family might be attributed to a case of incidental malignant arrhythmia. However, FLNC p.A1979T has failed to elucidate the DCM of the mother.…”
Section: Discussionmentioning
confidence: 90%
“…Neethling, et al reported that KCNE2, which is a voltage-gated potassium channel and functions in ven-tricular repolarization, interacted with FLNC. 28) Given the collective evidence, the sudden deaths in this family might be attributed to a case of incidental malignant arrhythmia. However, FLNC p.A1979T has failed to elucidate the DCM of the mother.…”
Section: Discussionmentioning
confidence: 90%
“…The association of FLNC with channelopathies has been described by Neethling et al in 2016 who reported an interaction between FLNC and KCNE2 (potassium voltage-gated channel) known to be causative for LQTS. In particular, they stressed this functional modulation under conditions of hypoxia and concluded that this pathway is likely to be involved in LQTS pathogenesis [ 43 ]. It is worth noting that in our patients with long QT, we did not observe likely pathogenic, nor pathogenic variants of the gene panels for congenital LQTS.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of stress, ECM proteins can drive cell biological responses with an important role in the tissue remodeling ( Jourdan-Lesaux et al, 2010 ; Frangogiannis, 2017 ; Frangogiannis, 2019 ). Under hypoxic stress, filamin-C interacted with other molecules to restore cellular membrane integrity, thereby promoting cellular survival during these conditions ( Leber et al, 2016 ; Neethling et al, 2016 ). Overall, it may be envisioned that ribosomal proteins, apoptosis related proteins and ECM proteins are secreted from MSCs and involved in the repair process of HLI.…”
Section: Discussionmentioning
confidence: 99%